Determination of liberated mercury from amalgam submerged in artificial saliva by cold vapor atomic absorption spectrometry - Vásquez, Aracelis; Fernández, Denny; Bello, Sorely; Ocando, Ana; Rodríguez, Minerva; Semprún, Blanca; Hernández, Maigualida; Colina, Marinela; Granadillo, Víctor (Ciencia, 1970)
Mercury might be liberated from dental amalgam in toxic amounts for humans, which represent a real health risk. This work presents the direct determination in vitro liberated mercury from amalgam submerged in artificial saliva by cold vapor atomic absorption spectrometry (CVAAS). Artificial saliva was prepared with KCl, KSCN, NaHCO3, NaH2PO4.H2O and lactic acid. The amalgams prepared with different types of trituration: few (F), normal (N) and excessive (E), were submerged in 10 mL of artificial saliva in tubes of 2.5 x 9.0 cm with cap and put into thermostated bath at 37°C. The total portions of test of saliva were took every 24 h the first three days and then every three days until completing 30 days; moving away the carved tooth of the saliva and storing this to 4°C until their spectrometric analysis. The precision were evaluated by mean of the Hg determination in 4 real samples, the results show average RSDs less than 5%. The accuracy was verified by analyzing two certified materials, comparing the target and experimental values, and obtaining mean relative error less than 5%. Additionally, the recovery studies were carried out, obtaining recoveries of 102 Ó 2%. Detection limit and characteristics mass were 0.30 ng Hg/L and 4.4 ng, respectively. Liberated mercury concentrations found in artificial saliva did not show significant statistically differences respect to the types of trituration employed. CVAAS-based method for the direct determination of Hg in artificial saliva was accuracy, precise and free from interferences.